Apropriação de inventos pelas fundações de amparo à pesquisa - Santana, Roquelina (2022)
Considering that the State Research Support Foundations financially support projects that may result in inventions that can be appropriated through patents, it was proposed in this paper to analyze how the regulations of the state research support foundations deal with the appropriation through patents arising from the results of projects supported by them and how many patents were deposited by each of them. To this end, the regulatory documents of the twenty-seven Brazilian state research funding foundations, established in the federative units in the period from 1960 to 2022, were researched regarding the possibility of appropriation of intellectual property rights, more specifically, the rights related to patents. A survey of the number of patent deposits and grants of these foundations was also carried out, allowing a comparison between the data. From then on, and based on the theoretical referential, the directives that permeate the appropriations of inventions of these foundations were listed, in addition to their characteristics, highlighting the differences between the foundations of support and support for research. Thus, this research is of an applied nature, with a quali-quantitative approach, of a descriptive character, based on documentary research procedures and technological prospection. The data portrayed that all the researched foundations were constituted by means of legal norms, and that, so far, only the six foundations Fundação de Amparo à Pesquisa do Estado da Bahia (FAPESB), Fundação de Amparo à Pesquisa do Estado de Goiás (FAPEG), Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), Fundação Carlos Chagas Filho de Amparo à Pesquisa do Rio de Janeiro (FAPERJ), the Fundação de Amparo à Pesquisa do Estado de Minas Gerais (FAPEMIG), and the Fundação de Amparo à Pesquisa do Estado do Rio Grande do Sul (FAPERGS), have a formal Intellectual Property policy document. It was also verified that the Fundação de Amparo à Pesquisa do Estado de São Paulo and Fundação de Amparo à Pesquisa do Estado de Minas Gerais have a significant number of patent deposits in contrast to the research support foundations located in the North region of Brazil that only the foundation established in the State of Pará participated in co-ownership, however, presented quantitative equal to 1 as a result.